Awareness and knowledge regarding Rota virus disease and vaccine among healthcare providers in tertiary care settings - Amna Yousaf Shah; Syed Hashim Ali Inam; Shanzay Jamal; Syed Jarrar Haider; Mishal Iqbal; Hamza Jamil (Journal of the Pakistan Medical Association, 2021)
Published in May - 2021